PLGA–PEG terpolymers as a carriers of bioactive agents, influence of PEG blocks content on degradation and release of herbicides into soil. (March 2019) - Rychter, Piotr; Lewicka, Kamila; Pastusiak, Małgorzata; Domański, Marian; Dobrzyński, Piotr
Abstract: Nowadays, researchers in the field of agrochemicals are trying to find effective methods to limit the excessive usage of pesticides and protect the environment. One of the most popular and promising techniques is the immobilization of pesticides using environment-friendly polymers. In the conducted research, it was demonstrated that the family of lactide/glycolide copolymers are unsuitable for this purpose due to very slow degradation in the soil. We examined influence of relatively small content of PEG blocks in newly synthesized poly(l -lactide-co-glycolide)-poly(ethylene glycol)–poly(l -lactide-co-glycolide) (PLGA–PEG–PLGA) on the degradation in soil, in activated sludge and usefulness of this terpolymers as a biodegraded carrier for the controlled release of two commonly used herbicides (Metazachlor and Pendimethalin). Presence of even small amount of PEG block in the terpolymer chain increases slightly the hydrophilicity of the polymeric chain, thereby increasing its susceptibility to hydrolytic and unexpectedly strongly to enzymatic degradation in soil environment. The amorphism of used as a carriers PLGA-PEG-PLGA terpolymers and the lack of the phenomenon of increasing the degree of crystallinity during degradation allow to achieve uniform progress of degradation, and thus is obtained a relatively constantly release of tested herbicides. In this way, it is possible to determine the optimal profile of degradation of polymer in soil and proper rate of diffusion and leaching of active agents which allows the release of herbicides in optimal and effective doses within 3–4 months of its application. Highlights: Preparation of high molecular terpolymers; L/lactide/glycolide/PEG with small content of PEG block (less than 16% w.). Comparison degradation rates of synthesized terpolymers PLAGA-PEG and copolymer PLAGA in water, in soil and in activated sludge. Comparative in vitro studies of metazachlor and pendimethalin release from the PLAGA – PEG terpolymers into soil or water. The PLGA-PEG terpolymer, interesting as a matrix, of systems for long lasting release of biologically active compounds, into the soil .